EFL STUDENTS’ PERCEPTION OF VIRTUAL LEARNING IN LISTENING CLASS: A CLASSROOM IMPLEMENTATION - Ulupi Sitoresmi; Irpan Yulianto; Imroatul Ma’fiyah (University of Kuningan, 2021)
This study aims to determine EFL students’ perception of virtual learning in listening class. It specifically describes on how higher education students perceive about the implementation and challenges towards virtual learning in listening class. This research employs a qualitative case study design. It involves several facets as the participants in order to obtain valid and reliable data to answer the research problems. The participants were 90 students and 2 lecturers taken from two different universities. From those amount of students, it was 50 students selected to meet the criterion of virtual learning implementation and the students’ responses profiling their perception of listening class. The findings about students’ perception of listening class are analyzed through the internal and external factors. Internal factors include students' physical condition, opportunities and motivation as well as students' perceptions of the level of difficulty in listening. External factors consist of learning materials, lecturers and teaching methods and the use of learning media. In the level of implementation and challenges, students thought that virtual learning is appropriate media of teaching listening during pandemic if lecturers are able to carry out their roles and students are always response the challenge adaptively in both terms of content and technology.